Improving school performance among Swedish foster children: A quasi-experimental study exploring outcomes of the Skolfam model. (November 2017) - Durbeej, Natalie; Hellner, Clara
Abstract: The educational underachievement of foster children has long been known and interventions aiming to improve school achievements in this population are highly warranted. The Skolfam model is a Swedish preventive approach with the primary goal to improve school performance among foster children. This quasi-experimental study aimed to explore the effects of Skolfam in comparison with the effects of ordinary support from the local community among foster children in Sweden. The study comprised one baseline assessment and one follow-up assessment, including both psychological and pedagogical outcome measures. In total, 91 foster children were included, of which 54 participated in the intervention group (Skolfam) and 37 participated in the comparison group. Children who had been given support in accordance with Skolfam showed minor improvements with weak effects on perceptual reasoning, general cognitive ability and literacy skills relative to the comparison group. These improvements were found regardless of gender, native language, signs of intellectual deficiency or having been replaced in a new foster home and/or in other societal care. For foster children in Sweden, the Skolfam model could be considered promising in improving school performance and may serve as a protective factor against adverse outcomes. Given the limited sample size, further research on this topic should be conducted before firm conclusions are drawn. Highlights: Foster children tend to be low achievers in school. We explored the effects of the Skolfam model among Swedish foster children. Improvements in cognitive ability, perceptual reasoning and reading skills were found. Skolfam showed weak effects in relation to the outcomes. Skolfam may be a promising intervention for Swedish foster children.